The battlefield of ballet schools: the commodification of dance education in China. Issue 5 (3rd September 2021) - Heyang, Tuomeiciren; Wang, Miao; Rowe, Nicholas
ABSTRACT: The involvement of venture capitalism within dance education in China is rapidly increasing, leading to significant shifts in understandings and practices of dance education as a private business. This article, therefore, explores this nexus of dance and the economy, advancing discussions from the commercialisation of dance education to the commodification of dance education. Drawing on a qualitative, ethnographic study of private dance schools in the rapidly expanding and economically prosperous city of Chengdu, we gather the perspectives and experiences of dance educators and venture capitalists. As they share their understandings of the commodification of ballet education, we focus on how such commodification is affecting dance education practices. Drawing on the experiences of our interviewees, we explore how capital is perceived to increase competition, which in turn brings a stronger consumer-orientation, which gives rise to expectations of certification from dance teaching. Through this critical analysis of the experiences and concerns of dance educators and venture capitalists, this research contributes to understandings of the interrelation between dance and economy in China. Given China's growing economic, political and cultural influence across the globe, this presents an urgent consideration for finance and the future of dance education around the world.